Genotypic response for stomatal conductance due to terminal heat stress under late sown condition in wheat (Triticum aestivum L.) - Ramya, K.T.; Jain, N.; Amasiddha, B.; Singh, P.K.; Arora, A.; Singh, G.P.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
Stomatal conductance (SC) was evaluated for thirty-six wheat (Triticum aestivum L.) genotypes sown during 2013-14 and 2014-15 under two dates of sowing. Steady state SC-1 leaf porometer was used to record SC on adaxial leaf surface at late boot (Z 49-50), early milk (Z 73) and late milk (Z 77) growth stages. In late sown conditions, the temperature was high (25.7 to 30.3Â°C) in boot stage itself and further increased during later stages (32 to 37.4Â°C). Under these conditions, the genotypes need to maintain an optimum range of stomatal conductance to maintain transpirational cooling without losing too much of water through transpiration. Heat susceptibility index ranged from 0.27 to 1.54 indicating levels of stress tolerance among the genotypes. Heat tolerant genotypes maintained relatively higher SC under heat stress over normal condition. Significant association between high SC with CT and grain yield was observed in all the three growth stages. The study was useful in detailed evaluation of SC and identification of genotypes with stable SC under heat stress. Genotypes KAUZ/AA//KAUZ, BERKUT and RAC 875, maintained high SC over the growth stages. Indian genotypes HD 2932, HD 2987, FLW-18, HW 2004 and RAJ 3765 were equally potential.